Role of apoptosis and microRNAs in identifying novel therapeutic targets in colon cancer - Borralho, Pedro Miguel Martinho, 1979- (2010)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2009